Cross-Border Integration through Contestation? Political Parties and Media in the Swiss–Italian Borderland. Issue 2 (3rd April 2017) - Mazzoleni, Oscar; Mueller, Sean
ABSTRACT: This article analyzes how, in the wake of the 2008 financial crisis, regional integration across an international border took place through political contestation. Although the crisis has been interpreted as leading to a revival of state borders, we show its differentiated impact on cross-border relationships at the heart of Western Europe, namely the Swiss–Italian borderland. A database encompassing over 1, 800 articles published in 11 different print and online newspapers over two years (2010–2012) allowed an analysis of the role played by political parties and the media as drivers of contestation. Our quantitative and qualitative analyses trace processes of both re-bordering ("Switzerland vs. Italy/the EU") and de-bordering (that is, integration across the border) through discourses prioritizing "the region." The wider implication from this study is that borderlands are subject to the same push- and pull-factors as states but that, additionally, a third dimension is present. Ignoring this intra-state center-periphery dimension means not fully capturing borderland dynamics, all the more so if political entrepreneurs skillfully seize spatial contention to advance their own conception of regional identity distinct from that of their nation-state.